Restrictive and non-restrictive relative clauses: a functional discursive perspective - Camacho, Roberto Gomes [UNESP] (Revista Virtual Estudos Linguagem, 2022)
This paper aims at describing the functioning of restrictive and non-restrictive clauses in Portuguese based on the application of the theoretical framework of Discourse Functional Grammar (Hengeveld; Mackenzie 2008). The analysis shows that a restrictive clause encodes semantic categories that modify the Np which they are part of, restricting their reference, while a non-restrictive clause encodes Discourse Acts, understood as pragmatic categories. What differs, therefore, a restrictive clause from a non-restrictive one, which gives the first a semantic nature, and the second a pragmatic nature, is that the restrictive clause, on the one hand, takes the intonational contour of the main clause, which is an integral part of; the non-restrictive one, on the other hand, has the status of Subsidiary Act or Aside of another nuclear Discourse Act, which is reflected in the prosody by its own intonation and, as such, codified by the Phonological Level. Because of this, the most evident morphosyntactic reflection of this distinction is that between the non-restrictive relative clause and the nuclear clause there is a one-way dependence, which corresponds to a Co-subordination relationship, unlike the restrictive relative clauses, which, constituting an integral part of the nuclear clause, consist of cases of Subordination.
Keywords: restrictive relative clause; non-restrictive relative clause; Subordination; Co-subordination